Online Learning Behavior During COVID-19 Pandemic toward Students' Digital Literacy Skills - Lestari, Intan; Setiawan, Wawan; Muqodas, Idat (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
COVID-19 pandemic changes the learning pattern is everywhere, including in Indonesia. This change raises problems in elementary school. This study analyzed online learning behavior in elementary school and the digital literacy skills of students during the Covid-19 pandemic in Indonesia. The descriptive qualitative research method with survey techniques toward 60 respondents was employed to investigate online learning behavior and digital literacy skills. The finding and data on digital literacy indicators show that the students have 8 elements of digital literacy, there are functional skills, creativity, critical thinking and evaluation, cultural and social understanding, collaboration, the ability to find and select information, effective communication, and e-safety. According to the data, the result shows that online learning behavior affects students' digital literacy skills.